Visible and hidden risk factors for banks - Til Schuermann; Kevin J. Stiroh (Federal Reserve Bank of New York, 2006)
This paper examines the common factors that drive the returns of U.S. bank holding companies from 1997 to 2005. We compare a range of market models from a basic one-factor model to a nine-factor model that includes the standard Fama-French factors and additional factors thought to be particularly relevant for banks such as interest and credit variables. We show that the market factor clearly dominates in explaining bank returns, followed by the Fama-French factors. The bank-specific factors are not informative, particularly for the largest banks, which take advantage of protection in the form of interest rate and credit derivatives. Even in our broadest model, however, considerable residual variation remains, with the mean pairwise correlation of residuals for the largest banks near 0.25. This finding suggests that important hidden factors remain. A principal component analysis shows that this residual variance is relatively diffuse, although the largest banks do tend to load in the same direction on the first component. Relative to the returns of large firms in other sectors, bank returns are relatively well explained with standard risk factors, and both the residual correlation and degree of factor loading agreement are not particularly large. These results have clear implications both for public policymakers seeking to quantify those shared bank exposures that create systemic risk and to portfolio managers seeking to devise optimal diversification strategies.
Keywords: G12; G21; 330; commercial banks; risk management; portfolio choice; systemic risk; Bank; Kapitalertrag; Risikomanagement; Portfolio-Management; USA